Pakistan Development Update, October 2014 - World Bank (Washington, DC, 2015)
For 2013 progress in Pakistan was significant and supported by a solid economic reform program of the Government of Pakistan. An IMF Extended Fund Facility (EFF) and two World Bank Development Policy Credits with a focus to restructure the energy sector, foster private and financial sector developments and improve social protection and revenue mobilization reinforced the reform program. The risk of a balance of payment crisis was minimized with a significant strengthening of the international reserves position. This mainly resulted from strong remittances and significant foreign capital inflows, which also brought stability in the foreign exchange market. A strong fiscal consolidation was achieved; the fiscal deficit was contained at around 5.5 percent of GDP - due to improved tax collection, high non-tax revenues, and restricted (current and development) expenditures. Price stabilization followed with average inflation remaining in single digits. This environment favored growth recovery, with the GDP growth rate above 4 percent for the first time in seven years - driven by dynamic manufacturing and service sectors supported by better energy availability and improved investors' expectations. As a result, performance under the IMF program remained satisfactory, with the Third Review concluded on June 27. However, since mid-August, the ongoing political uncertainty has negatively affected the macroeconomic stance and may modify the pace and depth of reforms. Some salient features of FY2013/14 economic performance were: growth re-emerged; increased remittances, capital and financial inflows supported a buildup of reserves; a significant correction of a previously loose fiscal stance took place; fiscal consolidation and improvement in business confidence produced a strong recovery in credit to the private sector, after five years of muted growth; price stability - with CPI inflation in single digit - was preserved; and progress on the structural reform agenda was promising. The political events following the mid-August Long-March and Sit-in may have affected the economy, and it also remains to be determined how much the pro-reform momentum, so carefully gathered during the past fiscal year and entering a decisive second year, will be affected by the civil unrest, but new investors' confidence-building measures will have to be nurtured to reinvigorate the reform agenda.